Development of yogurts with mixture of sheep and bovine milk: effect on chemical physical characteristics, protein profile and antioxidant activity (Research, Society and Development, 2022)
Yogurt is one of the most popular fermented dairy products and an excellent medium for new ingredients/food source. This study sought to evaluate and characterize bovine milk (BM) and sheep milk (SM) and yogurt made from bovine (BM) and sheep (SM) milk, and BM:SM mixture with the respective 100:0 fractions: 75:25, 50:50, 25:75 and 0:100, and evaluate their influence on physicochemical parameters, antioxidant, protein profile, microstructure and color analysis for yogurts. Yogurts with higher levels of acidity, protein, fat, total solids, ash and calcium were the ones made from SM.. Regarding the color attributes, all yogurts showed yellow-green characteristics after 21 days of storage by evaluating parameters a* and b*, with a predominance of bovine milk. The antioxidant profile showed a higher concentration at 100:0 and 0:100, but bovine milk has a higher DPPH (2,2-diphenyl-1-picrylhydrazyl) value, while yogurts maintained constant DPPH values ​​during storage, being higher at 0:100. Scanning electron microscopy (SEM) showed that BM (100:0) has a more compact structure, possibly due to the larger size of the fat particles and the lower protein concentration compared to SM (0:100). Sheep milk presented better nutritional value, showing its potential in the manufacture of products.